Code-Switching Used by Agatha Chelsea in the Suara Berkelas Video Podcast - Ni Putu Ayu Suniwiartini; Ni Nyoman Padmadewi; Ni Luh Putu Sri Adnyani (Journal of Innovative and Creativity (Joecy), 2026)
This study was conducted to investigate the types and functions of code-switching used by Agatha Chelsea in the Suara Berkelas video podcast. This study employed a descriptive qualitative approach. The data were obtained from Agatha Chelsea’s utterances during the podcasts. Data collection was conducted through non-participant observation and documentation techniques, namely by watching and transcribing the video podcast, identifying utterances containing code-switching, and classifying and analysing them according to Poplack’s (1980) theory of types of code-switching and Gumperz’s (1982) theory of functions of code-switching. The results of this study revealed 413 instances of code-switching, comprising 35 instances of tag-switching, 47 instances of inter-sentential switching, and 413 instances of intra-sentential switching. The data showed that intra-sentential switching was the most frequent type of code-switching used by Agatha Chelsea during the podcasts. In addition, 288 functions of code-switching were identified, comprising 25 instances of quotation, 2 instances of addressee specification, 18 instances of interjection, 1 instance of reiteration, 27 instances of message qualification, and 215 instances of personalization vs. objectivization. The most dominant function was personalization vs objectivization, indicating that Agatha Chelsea tends to code-switch to express personal experience and feelings, convey opinions, and provide factual information.